DAMPAK PERTAMBANGAN TERHADAP LINGKUNGAN HIDUP DI KALIMANTAN SELATAN DAN IMPLIKASINYA BAGI HAK-HAK WARGA NEGARA - Nurul Listiyani (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
AbstractThe legal issues in this paper is about the mining activities increasingly uncontrollable that cause various effects for society and the life around of mine, including: environmental demage, high of pollution (soil, water and air) and resulting in disruption to the wide of society such as damage of houses and public facilities, mainly by the action of blasting dynamite to open the mine site. Disruption aspects of community life, when the viewed of side of Human Rights, which is mainly related to economic rights, social and cultural, surely very related to the impact of this coal mining. Because of human rights involve aspects the right of life and good life, safe and healthy which is the right to a good environment, healthy and regulated in the laws of the republic Indonesia of 1945.Keywords: Mining, Environment, Environmental Damage and Human Rights